Trigger factor accelerates nascent chain compaction and folding - Katharina Till; Anne-Bart Seinen; Florian Wruck; Vanda Sunderlikova; Carla V. Galmozzi; Alexandros Katranidis; Bernd Bukau; Günter Kramer; Sander J. Tans (Proceedings of the National Academy of Sciences, 2025)
Conformational control of nascent chains is poorly understood. Chaperones are known to stabilize, unfold, and disaggregate polypeptides away from the ribosome. In comparison, much less is known about the elementary conformational control mechanisms at the ribosome. Yet, proteins encounter major folding and aggregation challenges during translation. Here, using selective ribosome profiling and optical tweezers with correlated single-molecule fluorescence, with dihydrofolate reductase (DHFR) as a model system, we show that the Escherichia coli chaperone trigger factor (TF) accelerates nascent chain folding. TF scans nascent chains by transient binding events, and then locks into a stable binding mode as the chain collapses and folds. This interplay is reciprocal: TF binding collapses nascent chains and stabilizes partial folds, while nascent chain compaction prolongs TF binding. Ongoing translation controls these cooperative effects, with TF-accelerated folding depending on the emergence of a peptide segment that is central to the core DHFR beta-sheet. The folding acceleration we report here impacts processes that depend on folding occurring cotranslationally, including cotranslational protein assembly, protein aggregation, and translational pausing, and may be relevant to other domains of life.